2013
DOI: 10.1192/bjp.bp.111.107888
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of an Improving Access to Psychological Therapies service

Abstract: Improving Access to Psychological Therapies provided a service that was probably cost-effective within the usual National Institute for Health and Clinical Excellence (NICE) threshold range of £20 000-30 000, but there was considerable uncertainty surrounding the costs and outcome differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 13 publications
6
49
1
1
Order By: Relevance
“…Our estimated costs for health and social care in the CADET trial are similar to those reported in the IAPT service evaluation for IAPT service or comparator mental health-care services. 76 Furthermore, despite differences in the populations, the QALY gain from the collaborative care intervention is in a similar range to that reported in an evaluation of therapist-delivered cognitive-behavioural therapy for depression, 77 in which the mean incremental QALY benefit was reported as 0.027 (95% CI -0.012 to 0.066).…”
Section: Economic Outcomessupporting
confidence: 52%
See 1 more Smart Citation
“…Our estimated costs for health and social care in the CADET trial are similar to those reported in the IAPT service evaluation for IAPT service or comparator mental health-care services. 76 Furthermore, despite differences in the populations, the QALY gain from the collaborative care intervention is in a similar range to that reported in an evaluation of therapist-delivered cognitive-behavioural therapy for depression, 77 in which the mean incremental QALY benefit was reported as 0.027 (95% CI -0.012 to 0.066).…”
Section: Economic Outcomessupporting
confidence: 52%
“…Although the mean QALY gain is modest, it is comparable, and favourable, to that recently reported in the evaluation of a UK Improving Access to Psychological Therapies (IAPT) service, 76 which estimated a mean EQ-5D QALY gain of 0.014 (SF-6D gain of 0.008). Our estimated costs for health and social care in the CADET trial are similar to those reported in the IAPT service evaluation for IAPT service or comparator mental health-care services.…”
Section: Economic Outcomesmentioning
confidence: 65%
“…The cost-effectiveness of Improving Access to Psychological Therapies (IAPT) services within the UK is not established [III] (McCrone, 2013;Mukuria et al, 2013). For generalised anxiety disorder, cost-effectiveness studies provide evidence for the value of CBT, certain antidepressants, and pregabalin (Bereza et al, 2009;Heuzenroeder et al, 2004;Iskedjian et al, 2008;Jorgensen et al, 2006;VeraLlonch et al, 2010).…”
Section: Costs Of Illness and Costeffectiveness Of Treatmentmentioning
confidence: 99%
“…27,28 A recent economic evaluation of an IAPT demonstration site found that IAPT provided a service that was 'probably costeffective' within the usual NICE threshold range of £20 000-£30 000, although with considerable uncertainty surrounding the costs and outcome differences. 29 This evaluation considered the lack of inclusion of medication costs as a study limitation.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%